THE RELATIONSHIP BETWEEN BILINGUAL METHOD AND VOCABULARY SKILLS IN EARLY CHILDHOOD AT INTERNATIONAL KINDERGARTEN SCHOOLS IN MAKASSAR - Anugrah Murtini (Universitas Muhammadiyah Makassar, 2026)
influences children’s cognitive, social, and communicative competencies. In the era of globalization, bilingual ability has become increasingly important for young learners, particularly in international-based educational settings. Previous studies have generally reported that bilingual education contributes positively to children’s language acquisition; however, many of these studies focus broadly on bilingual learning without specifically examining how particular bilingual instructional practices such as code-switching and dual-language exposure affect English vocabulary development in Islamic kindergarten contexts in Indonesia. In addition, limited research has explored this issue within international Islamic early childhood institutions in Makassar, creating a gap in empirical evidence regarding the effectiveness of bilingual instructional implementation in such settings. This study aims to examine the relationship between bilingual instructional methods and the English vocabulary performance of children enrolled in international Islamic kindergartens in Makassar, Indonesia. The bilingual instructional methods investigated in this study include teachers’ use of code-switching between Indonesian and English during classroom interaction, as well as dual-language exposure through learning activities, classroom communication, songs, storytelling, and visual media Data were collected through classroom observations, teacher questionnaires, and English vocabulary tests designed to measure children’s word knowledge. The findings revealed a statistically significant positive relationship between bilingual instructional practices and children’s English vocabulary outcomes, with a Spearman correlation coefficient of ρ = 0.395 (p < 0.05). These results indicate that structured bilingual exposure and interactive language practices can support vocabulary acquisition in early childhood learners. The effectiveness of bilingual instruction was also influenced by teacher competence, engaging teaching strategies, and parental involvement in children’s language learning. The novelty of this study lies in its focus on specific bilingual instructional strategies—particularly code-switching and dual-language exposure—within international Islamic kindergarten settings in Makassar, an area that has received limited scholarly attention. This study therefore contributes empirical evidence to the field of early childhood bilingual education by demonstrating how contextualized bilingual practices can foster English vocabulary growth among young learners in Islamic educational institutions.